Conceptual Study of the Ijarah Contract in Modern Sharia Business in the Digital Economy Era - Duwi Lestari; Erwina Mutiara Sari; Cindi Melinda Sari; Dwi Ayu Widyaningsih; Roehana Rofaidatun Umroh (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2026)
This study aims to analyze the concept of the ijarah contract from the perspective of Islamic business, examine its implementation in modern business practices, and identify the challenges of its application in the development of the contemporary economy. This research employs a library research method with a qualitative approach through the analysis of books, scientific journals, DSN-MUI fatwas, and relevant laws and regulations. The findings indicate that the ijarah contract possesses high flexibility and relevance in modern Islamic business because it emphasizes the utilization of goods or services without transferring ownership rights. The implementation of ijarah has developed in various sectors, including Islamic banking, leasing, digital services, and platform-based economies. However, its application still faces several challenges, such as the complexity of digital transactions, ambiguity in the object of benefit, low literacy in Islamic economics, and the tendency to formalize contracts without strengthening the substantive values of Sharia principles. This study emphasizes that the ijarah contract should not merely be understood as a legal-formal instrument, but must also be implemented based on the principles of justice, transparency, and public benefit (maslahah). The main contribution of this research lies in strengthening the analysis of the ijarah contract within the context of modern digital business as part of the development of an adaptive and equitable Islamic economy.